Agent‐based computational model of retinal angiogenesis simulates microvascular network morphology as a function of pericyte coverage. (6th November 2017) - Walpole, Joseph; Mac Gabhann, Feilim; Peirce, Shayn M; Chappell, John C
Abstract: Objective: Define a role for perivascular cells during developmental retinal angiogenesis in the context of EC Notch1‐DLL4 signaling at the multicellular network level. Methods: The retinal vasculature is highly sensitive to growth factor‐mediated intercellular signaling. Although EC signaling has been explored in detail, it remains unclear how PC function to modulate these signals that lead to a diverse set of vascular network patterns in health and disease. We have developed an ABM of retinal angiogenesis that incorporates both ECs and PCs to investigate the formation of vascular network patterns as a function of pericyte coverage. We use our model to test the hypothesis that PC modulate Notch1‐DLL4 signaling in endothelial cell‐endothelial cell interactions. Results: Agent‐based model (ABM) simulations that include PCs more accurately predict experimentally observed vascular network morphologies than simulations that lack PCs, suggesting that PCs may influence sprouting behaviors through physical blockade of endothelial intercellular connections. Conclusions: This study supports a role for PCs as a physical buffer to signal propagation during vascular network formation—a barrier that may be important for generating healthy microvascular network patterns.